An update on continuous‐wave cyclophotocoagulation (CW‐CPC) and micropulse transscleral laser treatment (MP‐TLT) for adult and paediatric refractory glaucoma. Issue 5 (22nd November 2020) - Souissi, Soufiane; Le Mer, Yannick; Metge, Florence; Portmann, Alexandre; Baudouin, Christophe; Labbé, Antoine; Hamard, Pascale
Abstract: Purpose: Continuous‐wave cyclophotocoagulation (CW‐CPC) is often preferred to medical and surgical treatments for managing refractory glaucoma. This review summarizes diode CW‐CPC indications, history, histopathology, methods, efficacy and safety. It also provides an overview of the latest data available on micropulse transscleral laser treatment (MP‐TLT) that uses repetitive micropulses of diode laser energy in an off‐and‐on cyclical fashion. Methods: A literature review was conducted on transscleral CW‐CPC (CW‐TSCPC), endoscopic CPC (ECP) and MP‐TLT. Relevant series of adult and paediatric patients were included for assessing the procedures. Results: Regarding CW‐TCPC, highly variable success rates are reported in the literature, depending on the definition of success, type of underlying glaucoma, energy settings, follow‐up duration and retreatment rates. CW‐CPC often needs to be repeated, especially in paediatric patients. CW‐CPC exposes to risks of inflammation and chronic ocular hypotony or phthisis with irreversible visual loss. CW‐TSCPC has mainly been used in very severe forms of glaucoma, in painful eyes with limited visual potential or after filtering surgery failure. Published data on ECP are more limited but overall good success rates have been reported. Through the direct visualization of the targeted ciliary body in anatomically abnormal eyes, ECP is the preferred surgical procedure in paediatric refractory glaucoma. Complication rates are relatively low after ECP; however, large studies with long‐term follow‐up are needed. ECP may be used in difficult, refractory cases, but it is often used earlier when combined with cataract surgery. Despite limited data on the exact mechanism of action of MP‐TLT and a lack of standardization of laser settings, the first data from heterogeneous case series shows that it has a similar efficacy and a better safety profile compared to CW‐TSCPC in the medium term. Conclusion: Although they may lead to sight‐threatening complications, both CW‐TSCPC and ECP seem effective. ECP appears to be superior to CW‐TSCPC in paediatric refractory glaucoma. Unlike ECP combined with cataract surgery, evidence supporting a wider use of CW‐TSCPC and MP‐TLT in earlier stages of neuropathy is lacking. While it now appears that the safety profile of MP‐TLT is superior to that of CW‐CPC, robust prospective comparative studies including homogeneous and well‐defined cohorts of patients are still needed to confirm an at least comparable efficacy in the long term.